Hubungan Antara Pengendalian Diri dengan Perilaku Agresif pada Siswa Sekolah Menengah Atas - Anik Supriani; Irwan Hidayat; Agung Setiawan; Adyanata Lubis (Departement of Mathematics Education, 2023)
Education is the basis for individual progress, with education individuals will obtain various information and knowledge that can be used to develop themselves. In the process of developing, there will always be social interactions, so students need guidance to be able to reach this maturity, because there is still a lack of understanding, insight into self, environment, experience and determining direction in life. Adolescents can experience various psychosocial problems such as having a rude attitude, poor performance, anti-social behavior, experiencing depression and anxiety, disruptive behavior, and hostility between friends. One of the problems that can be experienced by adolescents is having aggressive behavior tendencies. Based on observations, some students engage in aggressive behavior such as making fun of, speaking harshly, lying, fighting the teacher, being nosy or disturbing their friends, and withdrawing or skipping school, this is caused by students who are unable to control themselves from aggressive behavior. This research is using descriptive quantitative method. The research instrument is by giving questionnaires to 120 respondents, namely high school students, and analyzed by normality test, linearity test, hypothesis testing. Based on the results of data analysis, the value of rcount 0.2505 > rtable 0.1496, it is concluded that the hypothesis is accepted, meaning that there is a significant relationship between self-control and aggressive behavior towards high school students.